2017
DOI: 10.1097/pts.0000000000000283
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Pharmacist Intervention to Reduce Medication Errors and Health-Care Resources Utilization After Transitions of Care: A Meta-analysis of Randomized Controlled Trials

Abstract: Objectives: Medication errors are common during transitions of care.The main objective of the current investigation was to examine the effectiveness of pharmacist-based transition of care interventions on the reduction of medication errors after hospital discharge. Methods:A systematic search was conducted to detect published reports of randomized trials using the National Library of Medicine's PubMed database, the Cochrane Database of Systematic Reviews, and Google Scholar inclusive to July 1, 2015. Search te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 31 publications
2
59
0
Order By: Relevance
“…Our study's findings match those of other recent systematic reviews. 7,11,[57][58][59][60] Rodrigues et al 7 examined the effect of pharmacy-supported transitions of care interventions and Community pharmacists and transitions: A systematic review found a 32% reduction in 30-day readmissions (odds ratio 0.68; 95% CI 0.61-0.75), 7 and Mekonnen et al 58 examined the impact of medication reconciliation programs at transitions of care and found a 19% reduction in readmissions (RR, 0.81; 95% CI 0.70-0.95) 58 ; however, neither study was focused on community pharmacy. McNab et al 60 examined community pharmacist involvement on medication reconciliation, but not exclusively, and found a 9% reduction in readmissions (RR, 0.91; 95% CI 0.66-1.25).…”
Section: Discussionmentioning
confidence: 99%
“…Our study's findings match those of other recent systematic reviews. 7,11,[57][58][59][60] Rodrigues et al 7 examined the effect of pharmacy-supported transitions of care interventions and Community pharmacists and transitions: A systematic review found a 32% reduction in 30-day readmissions (odds ratio 0.68; 95% CI 0.61-0.75), 7 and Mekonnen et al 58 examined the impact of medication reconciliation programs at transitions of care and found a 19% reduction in readmissions (RR, 0.81; 95% CI 0.70-0.95) 58 ; however, neither study was focused on community pharmacy. McNab et al 60 examined community pharmacist involvement on medication reconciliation, but not exclusively, and found a 9% reduction in readmissions (RR, 0.91; 95% CI 0.66-1.25).…”
Section: Discussionmentioning
confidence: 99%
“…The role of pharmacists has been shown to be critical in reducing medication errors. For instance, a meta-analysis of 13 studies found that pharmacist intervention led to a 37% reduction in medication errors [26].…”
Section: Discussionmentioning
confidence: 99%
“…A metaanalysis of randomized controlled trials revealed that pharmacist-based interventions substantially decreased the number of medication-related problems and subsequent emergency department (ED) visits but could not decrease hospital readmission rates. 9 More recently, a large randomized trial was published that compared usual discharge care with pharmacist discharge medication review or extensive intervention (discharge medication review plus motivational interviewing and pharmacist involvement in primary care appointment). This study revealed that both 30-and 180-day ED visits and readmissions were substantially decreased in the extensive care arm compared with the usual care or discharge medication reconciliation only arms.…”
Section: Introductionmentioning
confidence: 99%